Current perspectives on customized fiberglass posts with composite resin: a literature review (Research, Society and Development, 2022)
Objectives: The present literature review aimed to verify in the current literature the applicability of customizing prefabricated fiberglass posts with composite resin for clinical situations. Materials and methods: A search was made in the PubMed database using the keywords: Non-vital tooth, Post and Core Technique and Composite Resins. The search was limited to the period from 2015 to 2021, of studies published in full, in English and free access. Results: 1,981 papers were obtained from PubMed, 429 from 2015 to 2021. After reading the titles and abstracts, 422 articles were excluded. In the end, 5 articles were selected, being later added 4 articles by cross-reference, totaling 9 articles. Conclusion: Custom prefabricated fiberglass posts with composite resin are a viable option for the rehabilitation of endodontically treated teeth with wide and/or fragile canals.